Pemanfaatan Ikan Tuna Menjadi Siomay untuk Meningkatkan Pendapatan Keluarga - Rugaya H. Serosero; Martini Djamhur (Universitas Mataram, 2021)
Tuna is one of the mainstay products of North Maluku. Diversification of processed tuna is a creation so that tuna can be enjoyed by all circles, both children and adults. The purpose of this service is to provide knowledge about the benefits of tuna and improve the skills of partners in processing siomay with various flavors so that they can increase their income. The method used in this activity is socialization and demonstration. The participation of the participants the very good to that the activity ran smoothly. With this activity, the partners understand more about the health benefits of tuna and increase their skills in processing siomay with various flavors. Furthermore, his skills can to applied to a small-scale business.